Self-report juvenile victimization in Portugal: findings from the third International Self-Report Delinquency study (ISRD-3) - Martins, Paula Cristina (2017)
Objectives: To analyze lifetime prevalence of juvenile victimization (overall and specific types), by city size, gender and age group. Method: A random selection of schools in 3 cities was followed by a random selection of 7–12 grade classes. Lifetime prevalence of victimization experiences (robbery, assault, cyber bullying, hate crime, parental violence and parental maltreatment) was assessed by a questionnaire administered in the classroom. 4124 students completed the questionnaire and 4048 were rated as valid for analysis, with 12 to 21 years of age (M = 15.3, SD = 2.1); 53.3 % were female and most were born in Portugal (95.1 %). Results: The prevalence of victimization ranged from 4.1% (assault and hate crime) to 29.3% (theft). Half of the participants reported having suffered one (25.5%) or more victimization experiences (24.5%). The proportion of victims ranged from 42.1% in the small city to 62.5% the large city. Hate crime and theft were the least and the most reported types of victimization, regardless of city size. No association was found between gender and overall (boys 50.4%; girls 49.8%) or less severe (boys 46.7%; girls 48.4%) victimization. However, boys were more likely to be victims of more severe crimes than girls (21.5% and 13.5%, respectively). Hate crime and assault were the least reported types of victimization by boys (3.8%) and girls (3.3%), respectively. Similar results were noted for younger (12-15 years: 2.9%) and older students (16-21 years: 5.3%). Theft was the most reported type of victimization by both genders (boys: 29.1%; girls: 29.4%) and age groups (12-15 years: 25.5%; 16-21 years: 33.7%). Older students had a higher probability of being victims than younger students, regardless of crime severity. Conclusions: Experiences of victimization occur throughout adolescence. Less severe types are more frequent than more severe ones. Rates of victimization are higher in larger cities.